Edukasi dan Intervensi Gizi untuk Mencegah Stunting : Studi Kasus Program KKN New Zero Stunting Desa Jatiwangi - Supartono; Adelia, Putri; Savitri, Meidiana; Baskoro, Renaldi Adi; Mufidah, Anisatul; ., Khoerunnisa; Aprilia, Elsa; Hanif, Muhammad Ammar; Handayani, Anis Fadhillah Setya (CV. ITTC INDONESIA, 2024)
The KKN New Zero Stunting program in Jatiwangi Village implemented a holistic approach to stunting prevention, including participatory nutrition education, empowerment of nutrition cadres, and sensitive nutrition interventions. This case study analyzes the program's implementation using qualitative methods through in-depth interviews, participatory observation, and focus group discussions. Results show positive changes in community knowledge, attitudes, and nutrition practices. Socio-cultural factors such as the dominant role of parents and in-laws, perceptions of